Synthetic ocitocin in induced labor and its maternal and fetal repercussion/Ocitocina sintética no trabalho de parto induzido e suas repercussões materno-fetais - Kleviton Leandro Alves Santos; Cinthia Rafaela Barbosa Lima Farias; Jaylla Silva Cavalcante; Ewerton Amorim Santos; Jaqueline Maria Silva; Ana Paula Ramos da Silva Duarte (Universidade Estadual de Alagoas, 2020)
Synthetic oxytocin is a pharmacological method widely used to induce labor, when it does not occur physiologically due to some clinical or physical condition of the pregnant woman or the baby, but it happens that this drug can be used in an inadequate or unnecessary way during parturient care, and as a consequence, cause maternal and fetal problems. This study aims to know the maternal-fetal impacts resulting from the inadequate use of synthetic oxytocin in labor. This is an integrative review in SCIELO, VHL, LILACS, MEDLINE and ACADEMIC GOOGLE database, in English and Portuguese. Twelve articles published between 2010 and 2017 were selected. Synthetic oxytocin, when used improperly to induce labor, can cause serious maternal-fetal problems, such as: uterine hyperstimulation, uterine rupture, fetal distress, painful uterine contractions,hyponatremia, fetal hypoxia and acidemia, in addition to an increase inthe cesarean rate. Therefore, most of the time, these problems can occur due to the dosage of oxytocin and its infusion at the time of delivery, therefore, it is necessary to produce a standard protocol for careful evaluation of the pregnant woman, avoiding administration of oxytocin inadequate and unnecessary, improving care and providing safe delivery.